(3TQM eNJUQ efJgi hGdCed aj Ydei GdCUhd hGdLOd GdShds - (3bWH GdOjf eMeO Hf eSYhO GdTjQGRis; (3GHf GdMGLH , LeGd GdOjf CHh YeQh GHf GdMGLH, LeGd GdOjf CHh YeQh GHf GdMGLH,J (B646 (3g` s ((3YHO GdMb Hf SYjO Hf eMeO Hf YHOhf s)
(3ChdgG (B:s
(3Cbhd gPG gh GdUfa GdKGdK ai GdYGe hGdNGU s
(3BNQgG (B:s
(3aWdY Ydjg ef hLg CMSf hbhd CUM ced GdSaQ GdKGfi hgh BNQ GdOjhGf ef TQM cJGH eNJUQ efJgi GdShd s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B211 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B265s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds